Up to a Third of Renal Transplant Recipients Have Deficiencies in Cognitive Functioning. (December 2017) - Stoessel, Lisa; Schieber, Katharina; Jank, Sabine; Reber, Sandra; Grundmann, Franziska; Lueker, Christine; Vitinius, Frank; Paslakis, Georgios; Eckardt, Kai-Uwe; Erim, Yesim
Introduction: Kidney transplantation is beneficial in improving cognitive abilities in patients with chronic kidney disease; however, there is still uncertainty concerning which cognitive domains benefit and to what extent. Aim: In the present study, cognitive functioning of renal transplant recipients was compared to normative data. Sociodemographic and clinical parameters that were associated with low cognitive performance were identified. Design: A total of 109 renal transplant recipients (63% men) participated in the study, with a mean age of 51.8 (standard deviation [SD] = 14.2) years. The cognitive test battery consisted of measurements assessing memory, attention, executive function, reproductive, and deductive ability. Results: In all tests, participants showed mean scores ranging within 1 SD of the population means. However, except for tests measuring memory, the percentage of participants scoring more than 1 SD below normed means was higher than expected in a normal distribution of performance. In certain tests, up to a third of the participants scored below average. Participants with continuous low performance (11%) showed higher age, poorer education, a longer time since transplantation, higher serum levels of urea and creatinine, and were more likely to have a deceased donor allograft. Discussion: Altough cognitive performance in renal transplant recipients matches normative data and confirms former findings, the amount of patients scoring more than 1 SD below average suggests that there are a considerable number of patients whose cognitive performance in certain domains lies below those of the general population. The identified sociodemographic and biochemical factors might be helpful to identify renal transplant recipients at risk.